Reconnaissance study of organic geochemistry and petrology of Paleozoic-Cenozoic potential hydrocarbon source rocks from the New Siberian Islands, Arctic Russia. (December 2016) - Sobolev, Peter; Franke, Dieter; Gaedicke, Christoph; Kus, Jolanta; Scheeder, Georg; Piepjohn, Karsten; Brandes, Christian; Blumenberg, Martin; Mouly, Benoit
Abstract: A reconnaissance study of potential hydrocarbon source rocks of Paleozoic to Cenozoic age from the highly remote New Siberian Islands Archipelago (Russian Arctic) was carried out. 101 samples were collected from outcrops representing the principal Paleozoic-Cenozoic units across the entire archipelago. Organic petrological and geochemical analyses (vitrinite reflectance measurements, Rock-Eval pyrolysis, GC-MS) were undertaken in order to screen the maturity, quality and quantity of the organic matter in the outcrop samples. The lithology varies from continental sedimentary rocks with coal particles to shallow marine carbonates and deep marine black shales. Several organic-rich intervals were identified in the Upper Paleozoic to Lower Cenozoic succession. Lower Devonian shales were found to have the highest source rock potential of all Paleozoic units. Middle Carboniferous-Permian and Triassic units appear to have a good potential for natural gas formation. Late Mesozoic (Cretaceous) and Cenozoic low-rank coals, lignites, and coal-bearing sandstones also display a potential for gas generation. Kerogen type III (humic, gas-prone) dominates in most of the samples, and indicates deposition in lacustrine to coastal paleoenvironments. Most of the samples (except some of Cretaceous and Paleogene age) reached oil window maturities, whereas the Devonian to Carboniferous units shared a maturity mainly within the gas window. Highlights: Reconnaissance study of source rocks for the New Siberian Islands (Russian Arctic). Several good source rocks were identified in the studied Palaeozoic-Cenozoic section. The type III kerogen (humic, gas-prone) dominates across the New Siberian Islands. Mesozoic rocks reached the oil window, Palaeozoic rocks are within the gas window. Late Cretaceous and Paleogene source rocks are immature.